Pembuatan Aplikasi Augmented Reality Pembelajaran Hewan - Robert Hartono; Liliana Liliana; Yulia Yulia (Jurnal Infra, 2016)
Augmented Reality (AR) is a new information media that is being developed nowadays. ARis a technology that combines 2D or 3D virtual objects  in a real environment around us. AR can be used as animal learning media that can attract children attention. AR can  bring interactive learning efficient. Because children not only learn in theory only, but children are also available to see animal objects in 3D. Animal learning application will be made in thie thesis.This application is created using Vuforia library and Unity Engine, using the programming language C #. Application can display animals 3D objects and display information in English and Indonesian. Animals in this application are wolf, fox, elephant, lion, zebra, rhino.  The test result shown that the Vuforia library and Unity Engine can give good output animation and good information, where each marker that has been determined, can be recognized well. The test results also showed that the child's interest to applications is quite high, as much as 80% of the kids liked the design of applications, 70% of children do not experience problems in using the application, and 80% of children will use the application again.